Reply to "remark on group velocity, negative and ultra-high index of refraction in photonic band gap materials" - Ojha S.P.; Srivastava S.K. (My University, 2025)
S.P. Ojha and Sanjeev K. Srivastava have replied to the criticism made by Gómez et al. on the research research made by the formers on group velocity, negative and ultra-high index of refraction in photonic band gap materials. They have employed the usual definition of the effective refractive index, in the case of photonic band gap structures in accordance with the concept and terminology introduced by Prof. K. Sakoda. The interpretation of a negative phase index and a negative group index remains uncertain. The apparent conflict with spectral relativity may be due to inadequate interpretation or may be the first indication of the possibility of superluminal velocity. They state that the results obtained by them is correct.